Blockchain Technologies and IP Ecosystems: A WIPO White Paper. - World Intellectual Property Organization (World Intellectual Property Organization, 2022)
Blockchain is one of the frontier technologies which is significantly affecting the way businesses operate while revolutionizing numerous innovation ecosystems, including the intellectual property (IP) ecosystem. This white paper explores potential applications and opportunities presented by blockchain to the existing IP ecosystems. It also identifies the challenges and issues that should be addressed to determine feasibility and cost-efficiency.